The Effectiveness of Supervision Program At Madrasah Aliyah in Pesawaran Regency - Marmin, Marmin; Koderi, Koderi; Abdul Muin, Juhri; Syafe’i, Imam (Educational Management, 2020)
This study was aimed to uncover and describe the implementation of the supervision program at Madrasah Aliyah (Islamic Senior High School) in the Pesawaran Regency of Lampung, Indonesia. The study was focused on the preparation of the supervision program, the implementation of the supervision program, and the evaluation of the implementation results of the supervision program. The study employed the descriptive-qualitative approach with observation, interview, and documentation as the data collecting techniques. The data was analyzed through data reduction, data display, and conclusion and verification. The results of the analysis showed that 1) there were weaknesses found in the preparation of the supervision program, specifically in the patterns and content similarities of the supervisory documents and lack of consideration toward the differences of the levels of each madrasah unit; 2) the effectiveness of the supervision program implementation has been achieved because the supervisors have well implemented the stages of the supervision program through the integration of the principals and the teachers’ programs; 3) the evaluation of the implementation results discovered the supervisors’ discrepancy, standards, and real targets (performance) to be used as reference materials in the preparation of supervision program in the following year.